The Influence of Managerial Ownership and Institutional Ownership on Agency Costs (Studies on Manufacturing Companies in The Basic Industrial and Chemical Sectors Listed on The Indonesia Stock Exchange) - Ramon Arthur Ferry Tumiwa; Nova Christian Mamuaya (International Journal of Applied Business and International Management, 2018)
The purpose of this study is to examine and analyze: (1) the effect of managerial ownership on agency costs, (2) the effect of institutional ownership on agency costs, and (3) the effect of managerial ownership and institutional ownership simultaneously affect to agency costs. This research was conducted at the primary industrial sector and chemical of manufacturing companies that listed on the Indonesia stock exchange 2014-2016. The companies analyzed amounted to 18 companies determined based on sampling criteria. The analysis method used is panel data analysis by using Eviews 9 programming computer. The results of this study found that managerial ownership has an insignificant relationship with agency cost. The institutional ownership has an insignificant with agency costs. The managerial ownership and institutional ownership have no significant effect on agency costs, simultaneous.